Hyperbaric Oxygen Ameliorates Insulin Sensitivity by Increasing GLUT4 Expression in Skeletal Muscle and Stimulating UCP1 in Brown Adipose Tissue in T2DM Mice - Liu, Yuan; Zhang, Di; Yuan, Junhua; Song, Limin; Zhang, Caishun; Lin, Qian; Li, Manwen; Sheng, Zhi; Ma, Zhengye; Lv, Fengyuan; Gao, Guangkai; Dong, Jing (Frontiers in Endocrinology, 2020)
Hyperbaric oxygen (HBO) therapy is a treatment modality useful for diseases. Hypoxia could stimulate the induction of insulin resistance. Therefore, we sought to determine whether hyperbaric oxygen would ameliorate insulin sensitivity by promoting glucose transporter type 4 (GLUT4) expression in muscle and by stimulating UCP1 in brown adipose tissue (BAT) in a streptozocin (STZ)-induced type 2 diabetes mellitus (T2DM) mouse model. Male C57BL/6J mice were treated three times with low-dose of streptozocin (60 mg/kg, i.p.) and were fed with high-fat diets (HFD) to establish the T2DM model. HBO was administered daily as 100% oxygen at 2.0 atmosphere absolute (ATA) for 1 h for a week. We found that HBO significantly reduced blood glucose levels and attenuated insulin resistance in T2DM mice. HBO modulated food intake by influencing the activity of neuropeptide Y (NPY)-positive neurons in the arcuate nucleus (Arc). HBO treatment increased GLUT4 amount and level of phosphorylated Akt (p-Akt) in muscles of T2DM mice whereas this treatment stimulated the phosphorylation of AMPK in muscles of both T2DM and HFD mice. The morphological staining of BAT and the increased expression of uncoupling of protein 1 (UCP1) demonstrated the promotion of metabolism after HBO treatment. These findings suggest that HBO ameliorates insulin sensitivity of T2DM mice by stimulating the Akt signaling pathway and by promoting GLUT4 expression in muscle, and by increasing UCP1 expression in BAT.